Macrognathus aral (Bloch and Schneider 1801): Growth, condition, age, mortality, recruitment and exploitation in running and stagnant ecosystems in Gandak Basin, India: Life history of M. aral under running and stagnant ecosystems - Kumar, Ravi; A. K. Jaiswar; Laxmi Prasad; Sarma, Kamal; Asha T. Landge; B.B. Nayak; Ahirwal, S. K.; K.G. Mandal (Indian Journal of Fisheries, 2024)
Growth and fishery of Macrognathus aral were studied from an oxbow lake Matwali-Majhariya maun and the river Dhanauti in Gandak Basin, India based on 367 and 451 specimens collected from the oxbow lake and the river, respectively through weekly sampling from June 2020 to May 2021 . The length-weight relationship revealed negative allometric growth (b<3.0) as W= 0.0051*L (2.82) in lake and W= 0.0045*L (2.85) in the river. The relative condition factor Kn was found to be ≈1.0 in both the ecosystems. The age at length zero and the maximum age Tmax were estimated to be -0.312 year and 9.4 years in the lake and -0.328 year and 8.8 years in the river respectively. Growth parameters L∞ and ‘K’ were estimated to be 37.7 cm and 0.32 year-1 in the lake, and 34.3 cm and 0.34 year-1 in the river, indicating slow growing nature of the species. The mortality rates ‘M’ ‘Z’ and ‘F’ were determined to be 0.78, 0.95 and 0.17 per year in lake and 0.81, 97 and 0.16 per year in river. Recruitment analysis showed a single peak during August in both the ecosystems. Lopt was estimated as 20.8 cm in lake and 19.2 cm in river. Virtual population analysis (VPA) revealed highest fishing mortality observed in the length groups above 30.0 cm in both the ecosystems. The optimum level of exploitation (E0.5) was found to be 0.32 in lake and 0.34 in river, which was lesser than the current level of exploitation. The above finding will be useful for sustainable management and conservation of the species. Keywords: Age, Exploitation, Gandak Basin, Growth, Mortality, Macrognathus aral, Recruitment